Análise das áreas de proteção integral do Pampa – Argentina, Brasil e Uruguai - Gabriel, Alice Poche (2020)
Instituted with the objective of safeguarding natural environments from the excessive action of human beings, protected areas are currently presented as a growing tool to be used in global environmental conservation strategies. In this way, the research sought to answer the following question: do Protected Areas of the type of integral protection of the Pampa - Argentina, Brazil and Uruguay have similar characteristics and effectively fulfill their role of conservation and preservation of the Pampa? For this, initially, a search was made for different protection approaches in order to contemplate themes involving the protection of nature. Using the identification of protected areas in the Pampa territory, the typologies that have the greatest representativeness were analyzed and a mapping of plant formations was elaborated, in order to identify which areas are conserving remnants of native vegetation. In view of all the categories identified, the type of comprehensive protection in the National Park category was selected for the study. There are 64 areas of integral protection in the Pampa, of which 20 are in the Parks category, with 11 parks in Argentina, 6 in Brazil and 3 in Uruguay. For the selection of the Parks, the Management Plan was taken into consideration, a guiding document for the management and management of the Parks. We opted for the elaboration of our own methodology to analyze the management plans of each Park: Campos del Tuyú National Park in Argentina, Espinilho State Park in Brazil and Esteros de Farrapos National Park and Islas del Río Uruguay in Uruguay, as well as works field visits, access to online pages that promote and disseminate information about Parks and a questionnaire applied to managers. As for the application of the questionnaire, several means of contact with the Park manager were identified, through e-mail, official websites of the administration bodies of protected areas and even online social network pages (facebook). The questionnaire was sent to all possible means of contact, but unfortunately, only the return of the Manager of the Espinilho State Park in Brazil occurred. Some issues were discussed based on the analysis of management plans and official sites for each Park. From these data and together with the answers to the questionnaire, it was possible to list parameters to analyze and discuss the effectiveness of each Park in the conservation of the Pampa. The parameters analyzed were: creation process, administrative, environmental and financial. Given the above, the importance of fieldwork for the application of a questionnaire and knowledge of the context in which each Park is inserted in the Pampa territory is highlighted. Finally, it is believed that each of the analyzed Parks presents an affective conservation of the objective that is proposed in its management plan, which have a similar methodological script for reading data with information from the Parks and guidelines to be followed. In addition, it is clear that to ensure the existence of these Parks, it is necessary to strictly follow the management plans, develop strategic plans based on the context of each area, invest in employee training, encourage the involvement of society and promote the Parks.